Kreativitas Guru Pendidikan Agama Islam Dalam Pembelajaran Baca Tulis Al-Qur’an di SMP Negeri 18 Kota Bengkulu - Ima Tiana; Jumadi apriansyah Apriansyah (Yayasan Darussalam Bengkulu, 2025)
Developing creativity is based on the potential that exists within oneself, there is something that must be explored and the tone also comes from oneself and this is supported by experience. Creativity plays a very important role in the learning process because a creative educator is able to develop learning methods, use media and carry out classroom management well. The aim of this research is to determine the creativity of an Islamic Religious Education teacher in optimizing reading and writing the Koran and utilizing media and managing the class. This research uses a descriptive type of qualitative research, namely a type of research that requires researchers to go directly to the research location and see the condition of the field objects to be studied. Data collection used in this research is observation, interviews and documentation. Meanwhile, the data analysis technique used is qualitative data analysis in the nature of Miles and Huberman Sugiyono. Meanwhile, the data validity tests used are credibility, transferability, dependability and confirmability tests. The results of this research show that the creativity of Islamic Religious Education teachers in learning to read and write the Al-Qur'an at SMP Negeri 18 Bengkulu city is quite good because PAI teachers have the creativity to build enthusiasm for learning and motivate students to want to learn. PAI teachers use various methods and of course also vary. A teacher can be said to be creative when he is able to manage the class well